A review of the families, genera and species of Dicyemida Van Beneden, 1876 - Catalano, Sarah R. (Zootaxa, 2012)
The classification of the species in the phylum Dicyemida Van Beneden, 1876, a group of small organisms whichparasitise the renal appendages of benthic cephalopods, is reviewed. While dicyemid parasites have simple multicellularmorphology, their lifecycle is complex and it is uncertain whether their affinities are with the protozoans or metazoans.Hence they are commonly given an intermediate ‘mesozoan’ status. Although 112 species are described, confusion existsfor 20% of the taxa over the validity of certain families, genera and species, which has been attributed to incomplete andinformation-poor descriptions, loss of type specimens, errors in taxonomy and conceptual differences. The history ofdicyemids dating from the first known reference by Filippo Calvolini of Italy in 1787 is presented, along with thecharacteristics which are commonly used to classify genera and species. All species described to date are listed withreference to the original published records and the validity of ambiguous records is explored. A way forward usingalternative technologies such as molecular genetic methods based on next generation sequencing platforms is suggested,which may help to address unresolved systematic and life history questions surrounding this parasite group. This review aims to assist taxonomists to help unravel the confusion surrounding the poorly studied and little understood Dicyemida.